Securing the food systems of Asian mega-deltas for climate and livelihood resilience - Salahuddin, Ahmad (International Centre for Climate Change and Development (ICCCAD)., 2023)
Published in the special issue of the Climate Tribune for the 2023 Gobeshona Global Conference, the article provides a comprehensive overview of the CGIAR Initiative on Asian Mega-Deltas (AMD). The AMD initiative aims to create resilient, inclusive, and productive deltas, which maintain socio-ecological integrity, adapt to climatic and other stressors. Additionally, the article talks about AMD’s focus of work in Bangladesh, including the target geographic areas.